Stump treatment with the root rot antagonist phlebiopsis gigantea - Pettersson, Martin (2013)

(untitled)
Stump treatment today requires large quantities of clean water mixed with the protective product Rotstop, to fully cover the stump surface. In order to reduce the water consumption without reducing the coverage of the stump surface, the pressure in the stump treatment device can be increased. Therefore, the Phlebiopsis gigantea (Fr.) Jül. suspension used as a biological control agent to prevent Heterobasidion annosum (Fr.) Bref. infection was pressure-tested. The pressurized suspensions were compared with the control suspensions and the survival was monitored by measuring oidia germination on agar medium. Pressures up to 150 bars (15 000 kPa) were tested and showed no negative effects on the survival of the P. gigantea spores.